Met fiction in the Iraqi NovelThe Presentations ofIns - /, Iishraq kamil; /, Bushra Mahmoud (Al-Adab Journal, 2016)
The paper tries to expose the presentations of Meta-fiction in Iraqi novel , this term has been well known in the writing of Iraqi novel as its counterpart in western and Arabic novel. It described as a free experiment and an intentional play in the process of creativity. Under this kind of experiment , the novel transforms to think of itself which becomes its subject, and this is a new approach in the novel, when the novelists look for it, and enriching their works by seriousness and unusual creativity in novel writing. The paper consists of two parts and a conclusion : The first part: meta-fiction , its term and beginning , goals and characteristics. The first section : the term and its appearance. The second section: goals and characteristics . The second part: the presentations of Meta-fiction in the aspects of creative process .The first section :the presentations of Meta-fiction in mind of narrator and the reader .The second section: the presentations of Meta-fiction in the narrative text. The results of the paper insured that Meta-fiction has various roles and functions as portraying and its rhythm, as well as the variety of visions, narrative scenes, and breaking of the deluded realism, riding out an illusion and a the creative process , and following its imaginative realms and knowing the pattern of narration , its arrangement, negativity from reader’s mind ,and recall the reader